PENGARUH PRIVATE LABEL TERHADAP KESADARAN MEREK DAN CITRA MEREK PADA KONSUMEN HIPERMARKET (STUDI PADA GIANT DAN HYPERMART DI KOTA BANDUNG) - Aisah Asnawi (President University, 2016)
Private label brand is a product that can only be found in the retailer. The presence of private label is now well known and has a high achievement in some developed countries. As for Asia Pacific, especially Indonesia, private label still has not become the primary choice when shopping for consumers. Private label products to compete hard with the brand manufacturer. This research was conducted to determine customer perceptions of private label, brand awareness and brand image and analyze the influence of large private label brand awareness and brand image are partial. Kind of research is descriptive and research methods verifikatif with descriptive and explanatory survey. The data obtained through questionnaires, interviews, and observations in the field. The results of data collection with the primary data source obtained from the sample of 115 respondents. The method of analysis used is Structural Equation Modeling (SEM). Review of each indicator, the results show that respect to each indicator, the results show that the assessment of the private label, brand awareness and brand image falls into both categories. From the results of statistical tests in mind that private label has a significant influence on brand awareness and brand image are partial. For the highest impact found in the Giant hypermarket and the last impact found in the Hypermart.